(untitled) - Le, Quang Tri (Wageningen, The Netherlands, 1996)
The book is the author's doctoral thesis. The book offers the result of studies describing the process of interaction between farmers and experts in improving the use of acid sulphate soils and to point out difficulties encountered. Actual conditions for four major areas were described including variabilities. Four representative areas: Tan Thanh, Tri Ton, Phung Hiep, and Hong Dan in the Mekong Delta, Viet Nam were selected for this study. Physical conditions were defined in terms of soil properties, as reflected by soil classification, and hydrological conditions were defined by climate data including flooding. Methods for land improvement in different areas were first defined by describing and analyzing measures taken by farmers, and by next developing schemes for improvement, using expert knowledge. These schemes were expressed by decision trees as a part of expert systems. But many questions were left and a series of experiments was designed and executed to answer those questions that could not be answered by experts
Keywords: Soil acidity; Mekong river delta